Earliest axial fossils from the genus Australopithecus. Issue 132 (July 2019) - Meyer, Marc R.; Williams, Scott A.
Abstract: Australopitheus anamensis fossils demonstrate that craniodentally and postcranially the taxon was more primitive than its evolutionary successor Australopithecus afarensis . Postcranial evidence suggests habitual bipedality combined with primitive upper limbs and an inferred significant arboreal adaptation. Here we report on A. anamensis fossils from the Assa Issie locality in Ethiopia's Middle Awash area dated to ∼4.2 Ma, constituting the oldest known Australopithecus axial remains. Because the spine is the interface between major body segments, these fossils can be informative on the adaptation, behavior and our evolutionary understanding of A. anamensis . The atlas, or first cervical vertebra (C1), is similar in size to Homo sapiens, with synapomorphies in the articular facets and transverse processes. Absence of a retroglenoid tubercle suggests that, like humans, A. anamensis lacked the atlantoclavicularis muscle, resulting in reduced capacity for climbing relative to the great apes. The retroflexed C2 odontoid process and long C6 spinous process are reciprocates of facial prognathism, a long clivus and retroflexed foramen magnum, rather than indications of locomotor or postural behaviors. The T1 is derived in shape and size as in Homo with an enlarged vertebral body epiphyseal surfaces for mitigating the high-magnitude compressive loads of full-time bipedality. The full costal facet is unlike the extant great ape demifacet pattern and represents the oldest evidence for the derived univertebral pattern in hominins. These fossils augment other lines of evidence in A. anamensis indicating habitual bipedality despite some plesiomorphic vertebral traits related to craniofacial morphology independent of locomotor or postural behaviors (i.e., a long clivus and a retroflexed foramen magnum). Yet in contrast to craniodental lines of evidence, some aspects of vertebral morphology in A. anamensis appear more derived than its descendant A. afarensis .